2005
DOI: 10.4049/jimmunol.174.9.5288
|View full text |Cite
|
Sign up to set email alerts
|

A Novel E3 Ubiquitin Ligase TRAC-1 Positively Regulates T Cell Activation

Abstract: TRAC-1 (T cell RING (really interesting new gene) protein identified in activation screen) is a novel E3 ubiquitin ligase identified from a retroviral vector-based T cell surface activation marker screen. The C-terminal truncated TRAC-1 specifically inhibited anti-TCR-mediated CD69 up-regulation in Jurkat cells, a human T leukemic cell line. In this study, we show that TRAC-1 is a RING finger ubiquitin E3 ligase with highest expression in lymphoid tissues. Point mutations that disrupt the Zn2+-chelating abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…Recent studies indicate that several ubiquitin E3 ligases are involved in the regulation of innate immune signaling (16)(17)(18)(19)(20)(21). We previously reported that the E3 ubiquitin ligase RNF125 negatively regulates RIG-I signaling (17), and it has been reported that RNF125 is also a T-cell activator (23), which suggests the presence of plural functions of RNF125 in regulation of cell proliferation. To identify genes affected by RNF125, we conducted microarray analysis (mock-vs. RNF125-transfected 293T cells) and found the gene for TRIM23 up-regulated ∼3-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicate that several ubiquitin E3 ligases are involved in the regulation of innate immune signaling (16)(17)(18)(19)(20)(21). We previously reported that the E3 ubiquitin ligase RNF125 negatively regulates RIG-I signaling (17), and it has been reported that RNF125 is also a T-cell activator (23), which suggests the presence of plural functions of RNF125 in regulation of cell proliferation. To identify genes affected by RNF125, we conducted microarray analysis (mock-vs. RNF125-transfected 293T cells) and found the gene for TRIM23 up-regulated ∼3-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using a yeast-two hybrid screening, we isolated RNF125 as an interacting protein with UbcH8. RNF125, a RING motif containing proteins, can act as a ubiquitin E3 ligase (25). A schematic diagram of RNF125 and its mutants used in this paper are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RNF125 interacts with several E2 enzymes (25), and one of these enzymes most likely acts as an E2 for ubiquitin conjugation to RIG-I. To identify the E2 acting upstream of RNF125 in RIG-I conjugation, we performed an in vitro assay examining ubiquitin conjugation to RIG-I [see supporting information (SI) Fig.…”
Section: E2 Enzymes Involved In Ubiquitinmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the work on TCR signalling and T-cell activation has been focused on positive regulators [10][11][12][13] ; however, more attention has been paid to negative regulators of T-cell activation from the cell surface to the nucleus in recent years 14 . For example, CD45 and SH2 domaincontaining phosphatase-1 dephosphorylate lymphocyte-specific protein tyrosine kinase, resulting in the cessation of TCR signal 5,6 .…”
mentioning
confidence: 99%